Ketoconazole- and fluconazole-induced embryotoxicity and skeletal anomalies in wistar rats: a comparative study - Vanessa Cristiane de Santana Amaral; Guilhermino Pereira Nunes Junior (Brazilian Archives of Biology and Technology, 2008)
Ketoconazole and fluconazole are two broad-spectrum azole antifungals used for the treatment of superficial and systemic mycoses. Embryotoxicity and teratogenicity have been reported in some studies when those drugs are administered at high doses to pregnant rats. The aim of this study was to present a comparative study of embryotoxic effects as well as the skeletal anomalies in fetuses of Wistar rats which received ketoconazole and fluconazole at teratogenic doses on gestational days (GD) 6 through 15 (organogenesis period). On gestational day (GD) 21, the dams were euthanized and examined for standard parameters of reproductive outcome. Fetuses were stained with alizarin red and the bones of the head, trunk, forelimb and hindlimb were examined for detection of skeletal anomalies. The frequency of skeletal anomalies in the ketoconazole-treated group was significant when compared to the fluconazole and the control group. O cetoconazol e o fluconazol são dois antifúngicos azólicos, de amplo espectro, utilizados no tratamento de micoses superficiais e sistêmicas. Alguns estudos relatam a embriotoxicidade e teratogenicidade induzidas por estes fármacos quando os mesmos são administrados em altas doses a ratas prenhes. O objetivo deste trabalho foi apresentar um estudo comparativo dos efeitos embriotóxicos e das anomalias esqueléticas em fetos de ratas Wistar que receberam cetoconazol e fluconazol em doses teratogênicas do 6º ao 15º dia gestacional (GD) (período da organogênese). No 21º GD as ratas foram eutanaziadas e examinadas quanto aos parâmetros padrões de performance reprodutiva. Os fetos foram corados com vermelho de alizarina e os ossos da cabeça, do tronco e dos membros anteriores e posteriores foram examinados para a verificação de anomalias esqueléticas. A freqüência de anomalias esqueléticas no grupo tratado com cetoconazol foi significante quando comparada à dos grupos fluconazol e controle.